Proceedings of the Forty-Seventh Annual ACM Symposium on Theory of Computing 2015
DOI: 10.1145/2746539.2746622
|View full text |Cite
|
Sign up to set email alerts
|

High Parallel Complexity Graphs and Memory-Hard Functions

Abstract: Abstract. We develop new theoretical tools for proving lower-bounds on the (amortized) complexity of functions in a parallel setting. We demonstrate their use by constructing the first provably secure Memory-hard functions (MHF); a class of functions recently gaining acceptance in practice as an effective means to counter brute-force attacks on security relevant functions.Pebbling games over graphs have proven to be a powerful abstraction for a wide variety of computational models. A dominant application of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 38 publications
1
73
0
Order By: Relevance
“…Without this constraint it would be much easier, but also much less interesting, to prove our results. 1 Another aspect worth pointing out is that although the reversible pebble game is weaker than the standard pebble game, it is technically much more challenging to analyze. The reason for this is that a standard pebbling will always progress in a "forward sweep" through the graph in topological order, and so one can often assume without loss of generality that once one has pebbled through some subgraph the pebbling will never touch this subgraph again.…”
Section: A Our Resultsmentioning
confidence: 99%
“…Without this constraint it would be much easier, but also much less interesting, to prove our results. 1 Another aspect worth pointing out is that although the reversible pebble game is weaker than the standard pebble game, it is technically much more challenging to analyze. The reason for this is that a standard pebbling will always progress in a "forward sweep" through the graph in topological order, and so one can often assume without loss of generality that once one has pebbled through some subgraph the pebbling will never touch this subgraph again.…”
Section: A Our Resultsmentioning
confidence: 99%
“…Depending on the architecture, the costs vary significantly for the same algorithm A. For the ASIC-equipped attackers, who can use parallel computing cores, it is widely suggested that the costs can be approximated by the time-area product AT [9,11,28,35]. Here T is the time complexity of the used algorithm and A is the sum of areas needed to implement the memory cells and the area needed to implement the cores.…”
Section: Attackers and Cost Estimatesmentioning
confidence: 99%
“…A simple tradeoff for scrypt has been known in folklore and was recently formalized in [20]. Alwen and Serbinenko analyzed a simplified version of Catena in [9]. Designers of Lyra2 and Catena attempted to attack their own designs in the original submissions [20,25].…”
Section: Introductionmentioning
confidence: 99%
“…If we model the hash function H as a random oracle [12], then the sender must compute an expected 2 t hashes until she finds such a σ. 4 A useful property of this PoW is that there is no speedup when one has to find many proofs, i.e., finding s proofs requires s2 t evaluations. The value t should be chosen such that it is not much of a burden for a party sending out a few emails per day (say, it takes 10 seconds to compute), but is expensive for a Spammer trying to send millions of messages.…”
Section: Introductionmentioning
confidence: 99%
“…In [1] Abadi, Burrows, Manasse and Wobber observed that CPU speeds may differ significantly between different devices and proposed as an alternative measure the number of times the memory is accessed (i.e., the number of cache misses) in order to compute the proof. This approach was formalized and further improved in [19,55,21,4], which use pebbling based techniques. Such memory-hard functions cannot be used as PoS as the memory required to compute and verify the function is the same for provers and verifiers.…”
Section: Introductionmentioning
confidence: 99%